Feasibility of home delivery of pemetrexed in patients with advanced non-squamous non-small cell lung cancer. Issue 2 (August 2015) - Lal, R.; Hillerdal, G.N.; Shah, R.N.H.; Crosse, B.; Thompson, J.; Nicolson, M.; Vikström, A.; Potter, V.A.; Visseren-Grul, C.; Lorenzo, M.; D'yachkova, Y.; Bourayou, N.; et al.
Highlights: Feasibility + adherence to home delivery of maintenance pemetrexed CT was evaluated. Adherence rate up to Cycle 6 was 98.0% (95% confidence interval: 86.4%, 99.7%). Home delivery was feasible, safe and preferred by patients. Physicians were generally satisfied with distant patient management. Study offers reproducible model for home-based CT. Abstract: Objectives: To evaluate the feasibility and adherence to home delivery (HD) of pemetrexed maintenance treatment in patients with advanced non-squamous non-small cell lung cancer (nsqNSCLC). Materials and methods: Exploratory, prospective, single-arm, Phase II study in advanced nsqNSCLC patients, with an Eastern Cooperative Oncology Group (ECOG) performance status of 0/1 that did not progress after 4 first-line induction cycles of a platinum doublet. The first cycle of pemetrexed (500 mg/m 2 ) was hospital administered, further cycles were HD until progressive disease or discontinuation. Feasibility was assessed by the adherence rate to HD (probability of reversion to hospital administration or treatment discontinuation due to HD) as primary endpoint, and by health-related quality-of-life (HRQoL: EQ-5D, lung cancer symptom scale [LCSS]), satisfaction with HD, overall survival (OS), and safety. Results: 52 patients (UK & Sweden) received a median of 4 (range 1–19) pemetrexed maintenance cycles. Adherence rate up to Cycle 6 was 98.0% (95% confidence interval [CI]: 86.4%, 99.7%). All but 2 patients remained on HD. 1 patient discontinued after Cycle 1 (patient decision), and 1 after Cycle 6 (non-compliance with oral dexamethasone). 87% (33/38) of the patients preferred home to hospital treatment and in 90% (28/31) of cases, physicians were satisfied with distant management of patients. During HD Cycles 2–4 mean change from baseline ranged from 3.0 to 7.7 for EQ-5D visual analog scale. The 6-month OS rate was 73% (95% CI: 58%, 83%). 1 patient had an HD-related adverse event (device-related infection, Grade 2) and 1 patient died after Cycle 1, before HD, due to a possibly drug-related atypical pneumonia. Conclusion: HD of pemetrexed maintenance treatment in patients with advanced nsqNSCLC was feasible, safe, and preferred by patients, while maintaining HRQoL. Physicians were satisfied with distant patient management.